Conservative Interference Injection to Minimize Wi-Fi Sensing Privacy Risks and Bandwidth Loss - Aryan Sharma; Haoming Wang; Deepak Mishra; Aruna Seneviratne (Future Internet)
With the impending integration of sensing capabilities into new wireless standards such as 6G and 802.11 bf, there is a growing threat to public privacy. Recent studies have revealed that even small-scale activities, like keyboard typing, can be sensed by attackers using Wi-Fi Channel State Information (CSI) as these devices become more common in commercial spaces. This paper aims to model the minimum CSI data rate required to sense activities in the channel and quantifies the detection accuracy of WiFi-based keystroke recognition in relation to the CSI sensing data rate. Our experimental findings using commercial-off-the-shelf hardware suggest that interference can be used as a defence strategy to degrade the CSI data rate and prevent undesirable Wi-Fi sensing attacks. To achieve a reduced data rate, we propose an extension to Bianchi’s model of CSMA/CA systems and establish a new mathematical relationship between channel contention and the available CSI. This proposed relationship was empirically verified, and our contention-based defence strategy was experimentally validated. Experiments show that our contention-based defence strategy increases the chances of evading undesired WiFi-based keystroke recognition by around 70%. By leveraging prior work that shows a degradation in CSI quality with lower transmission rates, we show that conservative interference injection can sufficiently reduce sensing accuracy whilst maintaining channel bandwidth.